Brahma‐Related Gene‐1 (BRG1) promotes the malignant phenotype of glioblastoma cells. Issue 6 (2nd February 2021) - Wang, Yinan; Yang, Chuan He; Schultz, Andrew P.; Sims, Michelle M.; Miller, Duane D.; Pfeffer, Lawrence M.
Abstract: Glioblastoma multiforme (GBM) is an aggressive malignant brain tumour that is resistant to existing therapeutics. Identifying signalling pathways deregulated in GBM that can be targeted therapeutically is critical to improve the present dismal prognosis for GBM patients. In this report, we have identified that the BRG1 (Brahma‐Related Gene‐1) catalytic subunit of the SWI/SNF chromatin remodelling complex promotes the malignant phenotype of GBM cells. We found that BRG1 is ubiquitously expressed in tumour tissue from GBM patients, and high BRG1 expression levels are localized to specific brain tumour regions. Knockout (KO) of BRG1 by CRISPR‐Cas9 gene editing had minimal effects on GBM cell proliferation, but significantly inhibited GBM cell migration and invasion. BRG1‐KO also sensitized GBM cells to the anti‐proliferative effects of the anti‐cancer agent temozolomide (TMZ), which is used to treat GBM patients in the clinic, and selectively altered STAT3 tyrosine phosphorylation and gene expression. These results demonstrate that BRG‐1 promotes invasion and migration, and decreases chemotherapy sensitivity, indicating that it functions in an oncogenic manner in GBM cells. Taken together, our findings suggest that targeting BRG1 in GBM may have therapeutic benefit in the treatment of this deadly form of brain cancer.